2010
DOI: 10.1016/j.acha.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet transform on manifolds: Old and new approaches

Abstract: Given a two-dimensional smooth manifold M and a bijective projection p from M on a fixed plane (or a subset of that plane), we explore systematically how a wavelet transform (WT) on M may be generated from a plane WT by the inverse projection p −1 . Examples where the projection maps the whole manifold onto a plane include the two-sphere, the upper sheet of the two-sheeted hyperboloid and the paraboloid. When no such global projection is available, the construction may be performed locally, i.e., around a give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…In fact, it can be shown that the proposed kernel regression is equivalent to the wavelet transform. This mathematical equivalence eliminates the need for constructing wavelets using a complicated computational machinery as has often been done in previous studies (Antoine et al, 2010; Hammond et al, 2011; Kim et al, 2012) and offers a simpler but more unified alternative.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, it can be shown that the proposed kernel regression is equivalent to the wavelet transform. This mathematical equivalence eliminates the need for constructing wavelets using a complicated computational machinery as has often been done in previous studies (Antoine et al, 2010; Hammond et al, 2011; Kim et al, 2012) and offers a simpler but more unified alternative.…”
Section: Methodsmentioning
confidence: 90%
“…Furthermore, such basis functions are only orthonormal for data defined on the sphere and result in a less parsimonious representation for data defined on other surfaces compared to the intrinsic LB-eigenfunction expansion (Seo and Chung, 2011). To remedy the limitations of spherical wavelets, the diffusion wavelet transform on graph data structures has been proposed (Antoine et al, 2010; Coifman and Maggioni, 2006; Hammond et al, 2011; Kim et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The graph wavelets are generated by a wavelet operator expanded on eigenfunctions of the graph Laplacian. In [1], Antoine et al also studied continuous wavelet transforms on graphs, constructed by a generator in spectral domain. As an example, they introduced the Mexican hat wavelet formulated by the generator u 2 e Àu 2 that is the Fourier transform of the Euclidean MHW.…”
Section: Adapted Waveletsmentioning
confidence: 97%
“…Especially in real-life signal is usually a one-dimensional or two-dimensional curved manifolds. For example, various spirals, spiral surface, sphere surface, paraboloid, hyperboloid, rotating surface, [1][2][3]6 torus, in particular, the developable surface to be discussed in this paper. Fortunately, for wavelet on manifold, it is worth mentioning in recent years, there is a good phenomenon, that is a lot of scholars made efforts for the creation and development of "wavelet on manifold", and achieved gratifying results.…”
Section: Introductionmentioning
confidence: 99%